Od a) do c)
[tex]-7\frac{4}{9}-2\frac{1}{6}=-(7\frac{4}{9}+2\frac{1}{6})=-(7\frac{8}{18}+2\frac{3}{18})=-9\frac{11}{18}\\\\3\frac{1}{4}-8\frac{5}{6}=-(8\frac{5}{6}-3\frac{1}{4})=-(8\frac{10}{12}-3\frac{3}{12})=-5\frac{7}{12}\\\\-2\frac{3}{5}+7\frac{1}{3}=7\frac{1}{3}-2\frac{3}{5}=7\frac{5}{15}-2\frac{9}{15}=6\frac{20}{15}-2\frac{9}{15}=4\frac{11}{15}[/tex]
Od d) do f)
[tex]-3,12-6,1=-(3,12+6,1)=-9,22\\\\6,4-10,25=-(10,25-6,4)=-3,85\\\\4\frac{5}{6}-8,2=-(8,2-4\frac{5}{6})=-(8\frac{1}{5}-4\frac{5}{6})=-(8\frac{6}{30}-4\frac{25}{30})=-(7\frac{36}{30}-4\frac{25}{30})=-3\frac{11}{30}[/tex]